Spectroscopic, textural, electrical and magnetic properties of antimicrobial nano Fe(III) Schiff base complex. (14th April 2019) - Mousa, Emad S.; Mahmoud, Walaa H.
Abstract : A novel Schiff base ligand (L) was prepared through condensation of 2, 6‐diaminopyridine and dibenzoyl methane in a 1:1 ratio. This Schiff base ligand was used for complex formation reaction with Fe(III) chloride. The structures of the ligand and its complex were deduced from elemental analyses, mass spectroscopy, 1 H NMR, IR, UV‐Vis, electronic spectra, magnetic moment, molar conductivity measurements, thermogravimetric analyses and X‐ray diffraction. The molecular and electronic structures of both ligand and complex were optimized theoretically using density function theory (DFT) method. Moreover, the antimicrobial activities of the prepared compounds were studied and proven against some pathogenic bacteria. The Fe(III) complex had higher biological activity than that of the free ligand. Proceeding from the collected information, the properties of the complex were further investigated. The particle size was determined by dynamic light scattering technique to be 92.59 nm. Textural properties of the nano complex were studied by N2 adsorption to estimate the specific surface area, pore volume and pore size distribution. The pores in the complex were found in the micropore–mesopore range. Differential scanning calorimetric measurements reveal the existence of four endothermic peaks at 243.8, 308, 339.8 and 380.5 K. Dielectric properties and conductivity were scanned at different frequencies and temperatures. The dielectric constant reaches a peak value of 600 at ~390 K, 30 Hz. A cross‐over from the universal dielectric response to the super linear power law of conductivity was reported for this complex at T  ≤ 345 K. Finally, the AC‐magnetic susceptibility measurements were carried out in the low‐temperature region. The complex showed paramagnetic behavior with a slight change in the magnitude of its magnetic moment at T  = 244 K. Abstract : Novel Schiff base and its nano Fe(III) complex were synthesized and characterized by different physicochemical and textural tools. A cross over from the universal dielectric response to the super linear power law is reported for Fe(III)‐L. An insulator to semiconductor change takes place.